Parental Reported Bullying among Saudi Schoolchildren: Its Forms, Effect on Academic Abilities, and Associated Sociodemographic, Physical, and Dentofacial Features - Raghad S. Alabdulrazaq; Sanaa N. Al-Haj Ali (International Journal of Pediatrics)
Context. Bullying among schoolchildren is a serious phenomenon and a leading health concern. Aim. To determine the prevalence of bullying, its forms, and its effect on academic abilities and school attendance, as well as associated sociodemographic, physical, and dentofacial features among Saudi schoolchildren. Methods. This cross-sectional study recruited a sample of 1131 parents of schoolchildren 8-18 years old and requested them to complete internationally accepted questionnaires for their children. Chi-squared test and logistic regression analysis were used to analyze the data (p<0.05). Results. A majority (89.2%) of schoolchildren were bully victims. Physical bullying (48.9%) was the most common form of bullying. The youngest schoolchildren (8-11 years) and those who disliked school classes or neither liked nor hated them, as well as those who were truant from school, were more likely to be victims. In addition, those who had worse grades because of bullying and those who were very often bullied because of good grades or because they showed an interest in school were more likely to be victims. With regard to targeted physical features, teeth were the number one target, followed by the shape of the lips and strength, while tooth shape and color were the most common dentofacial targets, followed by anterior open bite and protruded anterior teeth. Boys and the youngest schoolchildren were more often subjected to bullying because of these features (p<0.05). Conclusions. The prevalence of bullying, mainly in a physical form, was high among Saudi schoolchildren, with a negative influence on students’ academic abilities. Problems related to teeth, in particular, which can be treated, were targets, mainly for boys and the youngest schoolchildren. More studies are required in Saudi Arabia to explore the issue further among schoolchildren themselves.